Determinasi kepuasan kerja dengan work engagement sebagai variabel mediasi - Desi Tri Kurniawati; Ni Nyoman Suliati (Universitas Kristen Maranatha, 2025)
This study examined the influence of quality work of life, employee empowerment, and career development on job satisfaction and the mediating function of work engagement in the relationship between quality work of life, employee empowerment, and career development on job satisfaction. The population of this study was all employees of PT Penamas Nusaprima located in Malang City, totaling 215 employees, and based on the Slovin formula used, the sample in this study was 140 employees. The research method used is quantitative with an explanatory research approach using partial least squares-structural equation modeling (PLS-SEM) analysis techniques. The bootstrapping technique tests the hypothesis after the validity and reliability tests are carried out using an algorithmic approach. The results showed that quality work of life, employee empowerment, and career development, each have a positive and significant effect on job satisfaction, and it was found that work engagement acts as a partial mediator in the relationship between career development, employee empowerment, and quality work of life on job satisfaction.